2013
DOI: 10.1139/cjfas-2012-0265
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and economic drivers of the Bering Sea walleye pollock (Theragra chalcogramma) fishery: implications for the future

Abstract: This paper illustrates how climate, management, and economic drivers of a fishery interact to affect fishing. Retrospective data from the Bering Sea walleye pollock (Theragra chalcogramma) catcher–processer fishery were used to model the impact of climate on spatial and temporal variation in catch and fishing locations and make inferences about harvester behavior in a warmer climate. Models based on Intergovernmental Panel on Climate Change scenarios predict a 40% decrease in sea ice by 2050, resulting in warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…This study presents the first comprehensive analysis of variable spawning phenology for pollock. Previous studies focused in the Bering Sea have suggested that pollock spawn timing may be sensitive to temperature (Haynie & Pfeiffer, 2013;Smart, Duffy-Anderson, & Horne, 2012) and documented geographic variation in spawn timing among spawning groups experiencing different thermal regimes (Bacheler, Ciannelli, Bailey, & Duffy-Anderson, 2010;Jung, Kang, Kim, & Kendall, 2006), but the degree and form of thermal sensitivity was not quantified, and other (e.g., demographic) effects were not considered. In the Gulf of Alaska, some evidence for variation in spawn timing among years has been presented (Ciannelli, Bailey, Chan, & Stenseth, 2007;Yoklavich & Bailey, 1990); however, consideration of mechanisms has fallen outside the scope of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study presents the first comprehensive analysis of variable spawning phenology for pollock. Previous studies focused in the Bering Sea have suggested that pollock spawn timing may be sensitive to temperature (Haynie & Pfeiffer, 2013;Smart, Duffy-Anderson, & Horne, 2012) and documented geographic variation in spawn timing among spawning groups experiencing different thermal regimes (Bacheler, Ciannelli, Bailey, & Duffy-Anderson, 2010;Jung, Kang, Kim, & Kendall, 2006), but the degree and form of thermal sensitivity was not quantified, and other (e.g., demographic) effects were not considered. In the Gulf of Alaska, some evidence for variation in spawn timing among years has been presented (Ciannelli, Bailey, Chan, & Stenseth, 2007;Yoklavich & Bailey, 1990); however, consideration of mechanisms has fallen outside the scope of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to direct effects of climate on human behavior and resource acquisition activities (e.g. Carter & Letson, 2009;Haynie & Pfeiffer, 2013) or due to indirect effects of climate on the distribution and availability of resources, which then alter human behavior (e.g. Pinsky & Fogarty, 2012;Pinsky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The summer pollock fishery has displayed a movement northward, but surprisingly, this is correlated with colder temperatures later in the 2000s rather than with annual warmer temperatures (Haynie and Pfeiffer 2013), thus moving in the opposite direction to what might be expected on ecological grounds. The winter fishery has not displayed significant spatial shifts in the fishing grounds, largely because the location of spawning grounds has remained relatively constant and the fishery targets valuable roe-bearing fish in the southeastern Bering Sea.…”
Section: Ecosystem-human Couplingmentioning
confidence: 92%